2019
DOI: 10.1142/s012918312050028x
|View full text |Cite
|
Sign up to set email alerts
|

Elastic stiffness tensors of Zr–xNb alloy in the presence of defects: A molecular dynamics study

Abstract: In a nuclear reactor, the Zr-xNb alloy, which is used as a structural material in the core region, is irradiated by energetic particles that cause the atoms to be displaced from their lattice sites and giving rise to crystal defects. The local changes in the atomic arrangements lead to local deformations of the solid and thereby changes of its local mechanical properties. Understanding the mechanisms behind this evolution in the core region of a reactor, and its monitoring or controlling is a critical task in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The macroscopic properties of nuclear materials are highly sensitive to the microstructural evolution of atoms in the materials and other parameters such as temperature and pressure. The present authors have already studied the mechanical properties of Zr-1%Nb alloy in the presence of defects [9,10]. Also, other studies have been done by others [7][8][11][12][13][14][15][16][17][18][19][20] and some aspects of this alloy and other similar materials have been considered until now.…”
mentioning
confidence: 90%
“…The macroscopic properties of nuclear materials are highly sensitive to the microstructural evolution of atoms in the materials and other parameters such as temperature and pressure. The present authors have already studied the mechanical properties of Zr-1%Nb alloy in the presence of defects [9,10]. Also, other studies have been done by others [7][8][11][12][13][14][15][16][17][18][19][20] and some aspects of this alloy and other similar materials have been considered until now.…”
mentioning
confidence: 90%
“…The interatomic potential used for the Zr-Nb binary system was an angular-dependent potential (ADP) [22]. This kind of interatomic model potential has been mostly used for metals and metal alloys and it is a generalization of an embeddedatom model (EAM) potential that includes both dipole and quadrupole distortions of the local environment of an atom which has been shown to reproduce a wide range of properties [8]. The convergency of the size dependence of the simulation box for the calculation of impurity formation energy has been achieved for 2592 atoms in a 3×3×3 supercell composed of the unit cell with 96 atoms.…”
Section: Theories and Computational Detailsmentioning
confidence: 99%
“…Extensive research has already been conducted on the properties of zirconium-niobium alloys. For example, the evolution of mechanical properties with defects has been studied by some of the present authors [8][9]; the vacancy formation and self-interstitial clusterization under irradiation for pure zirconium have been studied by Maxwell and coworkers [10]; the mechanical properties of zirconium alloys and zirconium hydrides were studied by Weck and his coworkers [11]; according to Singh and colleagues, the fracture behavior of bi-crystalline zirconium-niobium alloys was examined with different niobium percentages [12]. Additional studies on the properties of Zr-Nb alloy and similar materials can be found in the literature [13][14][15][16][17][18][19][20].…”
Section: Introductionsmentioning
confidence: 99%
See 1 more Smart Citation